Fibroadipogenic progenitor cell response peaks prior to progressive fatty infiltration after rotator cuff tendon tear. Issue 12 (14th March 2022) - Sahai, Amil; Jones, Derek L.; Hughes, Marcus; Pu, Alex; Williams, Katrina; Iyer, Shama R.; Rathinam, Chozha; Davis, Derik L.; Lovering, Richard M.; Gilotra, Mohit N.
Abstract: Fibroadipogenic progenitor (FAP) cells are implicated as a major source of fatty infiltration (FI) in murine rotator cuff (RC) injury, but FAP cell response after RC tear in a rabbit model is unknown. This study determined whether changes in FAP cell count after an RC tear predate muscle degeneration in a clinically relevant rabbit model. We hypothesized increases in FAP cell count correlate temporally with RC degeneration. New Zealand white rabbits ( n  = 26) were evaluated at 1, 2, 4, and 6 weeks after unilateral full‐thickness tenotomy of supraspinatus and infraspinatus tendons. FI area and adipocyte size were histologically analyzed, muscle density was measured by computerized tomography, and quantification of FAP cells was measured by flow cytometry and immunohistochemistry. The percentage of intrafascicular adipocyte area increased over time in supraspinatus muscle samples ( p  = 0.03), significantly between 1‐ and 6‐week samples ( p  = 0.04). There were no differences in perifascicular adipocyte area percentages between time points. Peak increase in FAP cell count occurred at 1‐week ( p  = 0.03), with a decrease in the following weeks. There was a negative correlation between supraspinatus adipocyte area and FAP cell count ( p  < 0.05). On computed tomography (CT) scan, maximal decrease in muscle density was observed in the 4th to 6th weeks. In summary, FAP cell response occurred early after tenotomy and did not correlate temporally with increases in FI. This suggests that FAP cell response may predate degenerative changes, and early targeting of FAPs before adipocyte maturation could blunt FI after RC tear.